The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2020
DOI: 10.1248/cpb.c19-00784
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Nickel–Aluminium Complex Hydroxide for Adsorption of Chromium(VI) Ion

Abstract: In this study, nickel-aluminium complex hydroxides at different molar ratios (nickel-aluminium 1 : 2, 1 : 1, 2 : 1, 3 : 1, and 4 : 1, referred to as NA12, NA11, NA21, NA31, and NA41) were prepared, and their adsorption capability for chromium(VI) ion was investigated. Firstly, physicochemical characteristics (SEM images, X-ray diffraction (XRD) patterns, specific surface area, amount of hydroxyl groups, and surface pH) of nickel-aluminum complex hydroxide were evaluated. The amount of chromium(VI) ion adsorbed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…15) Our previous studies found that complex metal hydroxides (inorganic materials based on aluminum, iron, magnesium, and zirconium) were useful in removing heavy metals from aqueous media. [16][17][18][19][20][21] Additionally, the nickel-aluminum complex hydroxide showed superior adsorption performance on phosphate ions from an aqueous solution system. 22,23) However, there are lack of the reports regarding arsenic adsorption from aqueous solution systems.…”
Section: Introductionmentioning
confidence: 96%
“…15) Our previous studies found that complex metal hydroxides (inorganic materials based on aluminum, iron, magnesium, and zirconium) were useful in removing heavy metals from aqueous media. [16][17][18][19][20][21] Additionally, the nickel-aluminum complex hydroxide showed superior adsorption performance on phosphate ions from an aqueous solution system. 22,23) However, there are lack of the reports regarding arsenic adsorption from aqueous solution systems.…”
Section: Introductionmentioning
confidence: 96%